Parental smoking habits and children's exposure to household secondhand smoke in Klang Valley, Malaysia - Elsaihi, Wali Fatma Masoud (2024)
Secondhand tobacco smoke presents a significant threat to children’s health, particularly when caregivers smoke within the family home. Indoor smoking, especially by parents, has detrimental effects on children’s health. Addressing the escalating issue of indoor smoking among adults in Malaysia is vital, as it serves as a critical risk factor. There is a notable lack of research on how parental smoking affects children’s health, particularly regarding their addiction to nicotine and their parents’ attitudes. Furthermore, prior studies seldom focus on the influence of parental demographics in elucidating the effects of indoor smoking practices on children’s exposure to secondhand smoke. This study investigates the association between parental smoking practices and children’s exposure to secondhand smoke. It encompasses various determinants of parents’ indoor smoking behaviors, including their nicotine dependency, knowledge, attitudes, and smoking practices. Additionally, it explores how demographic factors may moderate the relationship between parental indoor smoking and the health risks children face from cigarette smoke exposure. Thus, this study proposes a health risk framework based on children’s reported health characteristics and levels of exposure. A cross-sectional study design was employed to collect data from 378 parents from four higher education institutions in the Klang Valley. The partial least squares technique and multiple linear regression were used to test the research hypotheses. The results underscore the significant impact of parents’ knowledge (β=0.154, t=2.314, p=0.021) and attitudes (β=0.276, t=5.526, p=0.001) on children’s exposure to secondhand smoke. The confluence of theoretical frameworks and empirical evidence can explain this influence. The Health Belief Model suggests that parents with greater knowledge of the dangers of smoking are more likely to perceive the health risks to their children as severe and actionable, leading to preventive measures. Moreover, these parents tend to adhere more closely to public smoking bans and household smoking rules, reducing the likelihood of secondhand smoke exposure. Regarding demographic factors, income significantly affects children’s exposure to secondhand smoke (β=-0.144, t=2.711, p=0.007). The negative β-coefficient indicates that as parents’ income increases, the children’s exposure to secondhand smoke decrease. This can be attributed to higher-income families having greater resources to mitigate exposure, such as residing in larger homes with separate smoking areas or having better access to educational materials. The multiple regression analysis showed that nicotine dependence had a positive and significant effect on children’s exposure to secondhand smoke (β=0.007, p=0.006). Conversely, parents’ knowledge negatively and significantly affected these risks (β=-0.475, p=0.001), while parents’ attitudes had a positive and significant impact (β=0.186, p=0.001). Participants’ smoking habits displayed a negative association with children’s exposure to secondhand smoke. However, this relationship was not statistically significant at the conventional 0.05 level (β=-0.04, p=0.079). Expert evaluation of the proposed framework considered criteria such as clarity, reliability, applicability, completeness, and sustainability. Eighty-four percent of the experts agreed on the framework’s clarity, suggesting that it was well understood and its objectives and components were clearly articulated. This study recommends the implementation of educational programs emphasizing the adverse effects on both parents’ and children’s health. Such programs can potentially be more effective in modifying parental behaviour, taking into account factors such as nicotine dependence, knowledge, and attitudes.